Preservation of Digital Archives: Systematic Literature Review - Namira Rahmi Zahara; Tamara Adriani Salim (D3 Perpustakaan Fakultas Vokasi Universitas Airlangga, 2022)
Background of the study: Digital archives in institutions or organizations has increased which is marked by the number of institutions that have established archive units. In the process of preservation or preservation of digital archives, it has its own difficulties compared to other media. Preservation is the most strategic activity, because the availability of records is closely related to the acquisition results that are maintained properly so that they can be processed and accessed for users. The implementation of archive preservation is not easy, there are several obstacles that cause the preservation to be less than optimal. Purpose: This study aims to provide knowledge about the preservation of digital archives as an effort to save important information and data in archives, it requires preservation or preserving archives in digital format. So that further research is needed, so this research is to facilitate researchers in conducting further research. Method: This study uses a systematic literature review method by combining bibliometric analysis of the literature from the Scopus database for the period 2018 to 2022. Findings: The results of the study show that preservation is an effort to maintain and store archives, both content or media so that they are durable and longer. Conclusion: Research topics in the search results regarding the preservation of digital archives are still found that have not been widely studied, namely, data preservation, long-term preservation, digital archives, and web archives, which can provide opportunities for further researchers to examine digital archive preservation